Airway management of an infant with Pierre Robin syndrome for mandibular distraction osteogenesis (Indian Journal of Case Reports, 2020)
Airway management of children with congenital craniofacial anomalies, especially those with Pierre Robin syndrome (PRS), which occurs in 1/8500–1/14,000 live births, is a challenge for the anesthesiologists. We report the case of a 60-day-old female PRS child who presented with severe upper airway obstruction and desaturation. The child underwent thin-sliced computed tomography followed by craniofacial reconstruction with mandibular distraction osteogenesis under general anesthesia. It is concluded that in children with PRS, securing airway even with fiberoptic bronchoscope can be difficult and may require additional airway assistance in the form of jaw thrust and tongue displacement during the procedure. Post-operative ventilatory assistance with nasal airway and continuous positive airway pressure may be helpful until effective mandibular distraction is achieved.